Infantile hemangioma as cause of neonatal gastrointestinal bleeding - Francesca Destro; Luciano Maestri; Claudio Vella; Vittoria Baraldini; Giovanna Riccipetitoni (Elsevier, 2018)
Introduction: Gastrointestinal infantile hemangiomas (IHs) are extremely rare and represent a diagnostic challenge, especially in newborns for the limited applicability of diagnostic approaches.We report two cases of neonates with gastrointestinal bleeding from intestinal hemangioma and a literature review of gastrointestinal IHs. Case 1: Full-term baby, asymptomatic at birth. On the seventh day of life she experienced failure to thrive, weight loss and hypotonus followed by melena and vomit. The imaging showed an intestinal vascular anomaly. We performed exploratory laparotomy and intestinal resection to remove the lesion. No complication occurred. Case 2: A 20-day old girl had melena and severe anaemia. The scintigraphic evaluation excluded gastric heterotopia. We opt for explorative surgery and we performed a laparoscopy that showed a congested and oedematous intestinal segment that was resected. Post-operative course was uneventful. Discussion: Gastrointestinal IHs may cause intractable bleeding, intussusception and intestinal perforations with bad prognosis. A prompt and accurate diagnosis is vital but not always easy. Colour-coded Duplex Scan are a good first-line imaging, MRI and CT give a better definition but the latter exposes to radiation. In the "era" of minimally invasive surgery, laparoscopy can have a role in the management of patients with gastrointestinal IHs. Conclusions: Gastrointestinal IHs should be considered in the differential diagnosis of neonates with anemia and gastro-intestinal bleeding. In selected cases, the minimally invasive approach permits diagnosis and treatment. Keywords: Gastrointestinal hemangioma, Neonates, Laparoscopy, Vascular anomalies, Gastrointestinal bleeding